Root traits of common bean genotypes used in breeding programs for disease resistance - Vieira, Rogério Faria; Carneiro, José Eustáquio Souza; Lynch, Jonathan Paul (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this work was to assess root traits of 19 common bean genotypes, used in breeding programs for disease resistance. Genotypes DOR 364 and G 19833 were used as deep and shallow basal root checks, respectively. The number of whorls and basal roots were assessed on five-day old seedlings grown in germination paper. Growth pouch studies were conducted to evaluate basal root gravitropism and lateral root length from primary roots, in seven-day old seedlings. The following root gravitropic traits were estimated: basal growth angle, shallow basal root length (localized in the top 2 cm), and relative shallow basal root growth. Number of whorls varied from 1.47 to 3.07, and number of basal roots ranged from 5.67 (genotype TO) to 12.07 (cultivar Jalo MG-65). Cultivars BRS MG Talismã, Carioca, BRS Pioneiro, and Diamante Negro exhibited shallow basal roots, while genotypes Vi-10-2-1, TU, AB 136, and México 54 showed deep basal roots. Cultivar Jalo MG-65 showed more lateral roots from the primary root than the other genotypes. Genotypes used on common bean breeding programs for disease resistance have great variability on basal and primary root traits.